Prey and Predators in Mathematical Model Under Caputo Fractional Derivative (Contemporary Mathematics, 2025)
The main concentration of ours as writers of this paper is finding the relation between two predators and one prey in a fractional mathematical model governed by Caputo fractional derivative (CFD). To achieve the above-mentioned goal the fractional reduced transform method (FRTM) has been utilized. When we use the CFD there will be no need to use Adomian's polynomials to calculate the nonlinear terms. To prove the reliability of CFD method, we have compared the outcomes of the fractional derivative orders with the ordinary derivative order index 0 < ω < 1. For further confirmation, we have presented our findings by showing graphs simulating the series solution. Moreover, we have also compared the error estimation with Rung Kutta and different orders. The Matrix Laboratory (MATLAB) software package was used as a tool for the above-mentioned process.
Keywords: fractional reduced differential transform method (FRDTM); CFD; prey predator model; MATLAB program